Dexmedetomidine Attenuates Myocardial Ischemia-Reperfusion Injury in Diabetes Mellitus by Inhibiting Endoplasmic Reticulum Stress. (30th November 2019) - Li, Jinjie; Zhao, Ying; Zhou, Nan; Li, Longyun; Li, Kai
Abstract : Objective. With the increasing incidence of diabetes mellitus (DM) combined with myocardial ischemia, how to reduce myocardial ischemia-reperfusion injury in DM patients has become a major problem faced by clinicians. We investigated the therapeutic effects of dexmedetomidine (DEX) on myocardial ischemia-reperfusion injury in DM rats and its effect on endoplasmic reticulum stress. Methods. SD rats with SPF grade were randomly divided into 6 groups: non-DM rats were divided into the sham operation group (NDM-S group), ischemia-reperfusion group (NDM-IR group), and dexmedetomidine group (NDM-DEX group); DM rats were divided into the diabetic sham operation group (DM-S group), diabetes-reperfusion group (DM-IR group), and diabetes-dexmedetomidine (DM-DEX) group, with 10 rats in each group. Then the effects of DEX on the changes of CK-MB and cTnT levels were examined. The effects of myocardial pathological damage and myocardial infarct size were detected. The apoptosis of cardiomyocytes was detected. The apoptosis of heart tissue cells was also tested through the expressions of cleaved caspase-3, Bcl-2, and Bax proteins. The expression of endoplasmic reticulum stress-related proteins GRP78, CHOP, ERO1 α, ERO1 β, and PDI was examined. The hypoxia/reoxygenation (H/R) injury cell model was established, the effects of DEX, DEX+ ERS agonist on cell apoptosis was also detected. Results . The myocardial damage of DM-IR was more severe than that of NDM-IR rats. DEX could reduce the expression of CK-MB and cTnT, reduce pathological damage, and reduce scar formation and improve fibrosis. DEX can reduce the expression of GRP78, CHOP, ERO1 α, ERO1 β, and PDI proteins in vivo and in vitro. And the effect of DEX on cell apoptosis could be blocked by ERS agonist. Conclusion. DEX attenuates myocardial ischemia-reperfusion injury in DM rats and H/R injury cell, which is associated with the reduction of ERS-induced cardiomyocyte apoptosis.